Is there a long-run relationship between taxation and growth: The case of Turkey - Katircio?lu, Salih (My University, 2010)
This paper empirically investigates long-run equilibrium relationship between economic growth and tax revenues in Turkey by using the bounds test and Johansen technique for cointegration. Results suggest that the existence of long-run equilibrium relationship between economic growth and taxation cannot be confirmed in the case of Turkey as a result of the bounds and Johansen tests for cointegration. Thus, further investigation such as error-correction modeling and/or causality analysis cannot be preceded between these two variables in the case of the Turkish economy.
Keywords: Growth; Long-run relationship; Taxation; Turkey